2018
DOI: 10.3892/ol.2018.9527
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features of T1 colorectal carcinomas with skip lymphovascular invasion

Abstract: With recent advances in endoscopic treatment, many T1 colorectal carcinomas (CRCs) are resected endoscopically with a negative margin. However, some lesions exhibit skip lymphovascular invasion (SLVI), which is defined as the discontinuous foci of the tumor cells within the colon wall. The aim of the present study was to reveal the clinicopathological features of T1 CRCs with SLVI and validate the Japanese guidelines regarding SLVI. A total of 741 patients with T1 CRCs that were resected surgically between Apr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Interestingly, both recurrences were T3 cancers despite negative vertical margins, possibly explained by other factors increasing risk of recurrence such as skip lymphovascular invasion or tumor budding beyond the resection margin. [17][18][19] In conclusion, the risk of recurrence within 12 months after a complete ESD with positive horizontal resection margins is very low for non-invasive lesions. Postponing the first follow-up endoscopy to 12 months after initial resection might be justified for non-invasive lesions.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, both recurrences were T3 cancers despite negative vertical margins, possibly explained by other factors increasing risk of recurrence such as skip lymphovascular invasion or tumor budding beyond the resection margin. [17][18][19] In conclusion, the risk of recurrence within 12 months after a complete ESD with positive horizontal resection margins is very low for non-invasive lesions. Postponing the first follow-up endoscopy to 12 months after initial resection might be justified for non-invasive lesions.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It is questionable whether this reflects the actual risk of recurrence within T1 CRCs, and therefore this requires further study. Interestingly, both recurrences were T3 cancers despite negative vertical margins, possibly explained by other factors increasing the risk of recurrence, such as skip lymphovascular invasion or tumor budding beyond the resection margin [17][18][19].…”
Section: Follow-up Time and Detected Recurrencementioning
confidence: 99%
“…Currently, there is a debate about the importance of the different histopathological criteria and their respective weight in assessing the risk of lymph node recurrence. While significant budding 5 19 20 21 22 , LVI 5 22 23 24 , and poorly differentiated components are clearly recognized as pejorative criteria, depth of invasion beyond 1000 µm is increasingly being questioned 5 25 . In the present study, no focal or metastatic tumor recurrence was reported for very low risk lesions considered cured by ESD; however, we cannot exclude a significant risk of recurrence, particularly for low risk lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the small sample size of our study, the discussion about the new threshold of acceptable sm invasion is open since none of the patients with LR T1 cancers with sm invasion between 1000 and 2000 m experienced recurrence or lymph node involvement. This 2000 m threshold has already been reported in a large Japanese study [24]. Systematically referring lesions with FDIP to surgical treatment may not be adequate, particularly for elderly patients or those presenting several comorbidities.…”
Section: Accepted Manuscriptmentioning
confidence: 90%
“…The study suggested that skip lymphovascular invasion was associated with hepatic metastasis in CRC cases. Yuta sato et al (19) have analyzed the clinicopathological features of T1 CRC with SLVI and indicated that lymphovascular invasion was a significant risk factor for SLVI in T1 CRC. The above three studies consistently implicated the possible existence of an undefined group of T1 CRC.…”
Section: Discussionmentioning
confidence: 99%